ADVOKASI HAK-HAK ISTRI DALAM RUMAH TANGGA PERSPEKTIF HUKUM ISLAM - Jamaa, La (Sunan Kalijaga State Islamic University & The Asia Foundation, 2016)
Marriage gives material and immaterial rights to the wife in the household. But in social reality, many wives do not enjoy the rights of material and non-material, because the husband does not carry out his obligations responsibly. Therefore, forms of Islamic legal protection of the rights of the wife must be studied. The analysis focuses on advocacy for the rights of wives for dowry, living fulfillment, and a sense of security, in the perspective of Islamic law, to better protect the wife.